Prognostic Value of Genomic Instability of m6A-Related lncRNAs in Lung Adenocarcinoma - Li, Rui; Li, Jian-Ping; Liu, Ting-Ting; Huo, Chen; Yao, Jie; Ji, Xiu-Li; Qu, Yi-Qing (Frontiers in Cell and Developmental Biology, 2022)
Genomic instability of N6-methyladenosine (m6A)-related long noncoding RNAs (lncRNAs) plays a pivotal role in the tumorigenesis of lung adenocarcinoma (LUAD). Our study identified a signature of genomic instability of m6A-associated lncRNAs signature and revealed its prognostic role in LUAD. We downloaded RNA-Sequencing data and, somatic mutation data for LUAD from The Cancer Genome Atlas (TCGA) and the GSE102287 dataset from the Gene Expression Omnibus (GEO) database. The “limma” R package was used to identify a network of regulatory m6A-related lncRNAs. We used the Wilcoxon test method to identify genomic-instability-derived m6A-related lncRNAs. A competing endogenous RNA (ceRNA) network was constructed to identify the mechanism of the genomic instability of m6A-related lncRNAs. Univariate and multivariate Cox regression analyses were performed to construct a prognostic model for internal testing and validation of the prognostic m6A-related lncRNAs using the GEO dataset. Performance analysis was conducted to compare our prognostic model with the previously published lncRNA models. CIBERSORT algorithm was used to explore the relationship of m6A-related lncRNAs and the immune microenvironment. Prognostic m6A-related lncRNAs in prognosis, the tumor microenvironment, stemness scores, anticancer drug sensitivity was analyzed to explore the role of prognostic m6A-related lncRNAs in LUAD..A total of 42 genomic-instability-derived m6A-related lncRNAs were differentially expressed between the GS (genomic stable) group and GU (genomic unstable) groups of LUAD patients. Four differentially expressed lncRNAs, 17 differentially expressed microRNAs, and 75 differentially expressed mRNAs were involved in the genomic-instability-derived m6A-related lncRNA-mediated ceRNA network. A prediction model based on 17 prognostic m6A-associated lncRNAs was constructed based on three TCGA datasets (all, training, testing) and validated in the GSE102287 dataset. Performance comparison analysis showed that our prediction model (area under the curve [AUC] = 0.746) could better predict the survival of LUAD patients than the previously published lncRNA models (AUC = 0.577, AUC = 0.681). Prognostic m6A-related-lncRNAs have pivotal roles in the tumor microenvironment, stemness scores, anticancer drug sensitivity of LUAD. A signature of genomic instability of m6A-associated lncRNAs to predict survival of LUAD patients was validated. The prognostic, immune microenvironment and anti-cancer drug sensitivity analysis shed new light on the potential novel therapeutic targets in LUAD.